B Cells Are Indispensable for a Novel Mouse Model of Primary Sjögren’s Syndrome - Zheng, Junfeng; Huang, Qiaoniang; Huang, Renliang; Deng, Fengyuan; Yue, Xiaoyang; Yin, Junping; Zhao, Wenjie; Chen, Yan; Wen, Lifang; Zhou, Jun; Huang, Renda; Riemekasten, Gabriela; et al. (Frontiers in Immunology, 2017)
Primary Sjögren’s syndrome (pSS) is characterized by a panel of autoantbodies, while it is not clear whether B cells and autoantibodies play an essential role in pathogenesis of the disease. Here we report a novel mouse model for pSS which is induced by immunization with the Ro60_316-335 peptide containing a predominant T cell epitope. After immunization, mice developed several symptoms mimicking pSS, including a decreased secretion of tears, lymphocytic infiltration into the lacrimal glands, autoantibodies and increased levels of inflammatory cytokines. Disease susceptibility to this novel mouse model varies among strains, where C3H/HeJ (H2-k) and C3H/HeN (H2-k) are susceptible while DBA/1 (H2-q) and C57BL/6 (H2-b) are resistant. Depletion of B cells using anti-CD20 monoclonal antibodies prevented C3H/HeN mice from development of the pSS-like disease. In addition, HLA-DRB1*0803, a pSS risk allele, was predicted to bind to the hRo60_308-328 which contains a predominant T cell epitope of human Ro60. Therefore, this study provides a novel mouse model for pSS and reveals an indispensable role of B cells in this model. Moreover, it suggests that T cell epitope within Ro60 antigen is potentially pathogenic for pSS.